The Influence of Students’ Perception and Learning Environment on Teachers’ Performance - Esy Marliah; Bukman Lian; Hery Setiyo Nugroho (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2026)
This study aims to analyze the influence of students’ perceptions and the learning environment on teacher performance at SMA Negeri 5 Palembang. A quantitative approach with a survey method was employed. Data were collected through questionnaires distributed to 120 randomly selected students across grades 10, 11, and 12. Multiple linear regression analysis was used to examine both simultaneous and partial effects. Findings reveal that (1) students’ perceptions significantly and positively influence teacher performance, indicating that favorable student views correspond with higher performance ratings; (2) the learning environment also significantly impacts teacher performance, with supportive, safe, and comfortable classroom conditions enhancing teacher effectiveness; and (3) both variables simultaneously exert a significant influence on teacher performance. The research uniquely positions students as active evaluators whose perceptions serve as meaningful performance indicators, while simultaneously examining the interplay between internal student perspectives and external environmental factors. Schools should systematically utilize student feedback as a reflective tool for teacher development and prioritize creating conducive physical and psychological learning environments to optimize teaching quality. The study contributes empirical evidence to educational management discourse, demonstrating that teacher performance improvement requires holistic attention to both student-centered feedback mechanisms and supportive institutional conditions.